Germinal Center-Induced Immunity Is Correlated With Protection Against SARS-CoV-2 Reinfection But Not Lung Damage. (20th November 2021) - Kim, Green; Kim, Dong Ho; Oh, Hanseul; Bae, Seongman; Kwon, Jisoo; Kim, Min-Jae; Lee, Eunyoung; Hwang, Eun-Ha; Jung, Hoyin; Koo, Bon-Sang; Baek, Seung Ho; Kang, Philyong; et al.
Abstract: Germinal centers (GCs) elicit protective humoral immunity through a combination of antibody-secreting cells and memory B cells, following pathogen invasion or vaccination. However, the possibility of a GC response inducing protective immunity against reinfection following severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection remains unknown. We found GC activity was consistent with seroconversion observed in recovered macaques and humans. Rechallenge with a different clade of virus resulted in significant reduction in replicating virus titers in respiratory tracts in macaques with high GC activity. However, diffuse alveolar damage and increased fibrotic tissue were observed in lungs of reinfected macaques. Our study highlights the importance of GCs developed during natural SARS-CoV-2 infection in managing viral loads in subsequent infections. However, their ability to alleviate lung damage remains to be determined. These results may improve understanding of SARS-CoV-2–induced immune responses, resulting in better coronavirus disease 2019 (COVID-19) diagnosis, treatment, and vaccine development. Abstract : Recovery from natural SARS-CoV-2 infection may induce a protective germinal center-induced immunity against reinfection.